2010
DOI: 10.1007/s12282-010-0234-5
|View full text |Cite
|
Sign up to set email alerts
|

Role of stromal myofibroblasts in invasive breast cancer: stromal expression of alpha-smooth muscle actin correlates with worse clinical outcome

Abstract: Myofibroblasts represent an important prognostic factor for invasive growth that is translated into a poor clinical prognosis for patients with invasive breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
124
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(144 citation statements)
references
References 19 publications
10
124
1
2
Order By: Relevance
“…In addition, multivariate analysis showed that SDF-1 status was also an independent factor related to overall survival in patients with ER-positive tumors, and therefore stromal SDF-1 status could have a significant prognostic value and may be clinically useful for assigning adjuvant therapy to patients with ER-positive invasive breast cancers (Kobayashi et al, 2009). Recently Yamashima and colleagues showed that the expression of the other important hallmark of myofibroblasts, a-SMA, correlates with invasive growth and poor clinical prognosis (Yamashita et al, 2010). Likewise, patients with stroma rich-tumors had a shorter relapse-free period and overall survival compared to stroma-poor tumors (de Kruijf et al, 2011).…”
Section: Cafs As Marker Of Patient Prognosismentioning
confidence: 99%
“…In addition, multivariate analysis showed that SDF-1 status was also an independent factor related to overall survival in patients with ER-positive tumors, and therefore stromal SDF-1 status could have a significant prognostic value and may be clinically useful for assigning adjuvant therapy to patients with ER-positive invasive breast cancers (Kobayashi et al, 2009). Recently Yamashima and colleagues showed that the expression of the other important hallmark of myofibroblasts, a-SMA, correlates with invasive growth and poor clinical prognosis (Yamashita et al, 2010). Likewise, patients with stroma rich-tumors had a shorter relapse-free period and overall survival compared to stroma-poor tumors (de Kruijf et al, 2011).…”
Section: Cafs As Marker Of Patient Prognosismentioning
confidence: 99%
“…It was also noted that there was no significant interstitial myofibroblast proliferation in a small number of diffuse, poorly differentiated gastric cancer cases, which may reflect individual differences in the pathogenesis of gastric cancer. It has been shown that there were large differences in the interstitial myofibroblast number among different cases of breast and bladder cancer [29,30]. Some studies have found that α-actin expression is related to the depth of invasion or lymph node metastasis of the gastric cancer, suggesting that gastric interstitial myofibroblasts were involved in gastric cancer invasion and metastasis (29,31).…”
Section: Relationship Between α α-Actin Expression Of Myofibroblasts mentioning
confidence: 99%
“…It has been shown that there were large differences in the interstitial myofibroblast number among different cases of breast and bladder cancer [29,30]. Some studies have found that α-actin expression is related to the depth of invasion or lymph node metastasis of the gastric cancer, suggesting that gastric interstitial myofibroblasts were involved in gastric cancer invasion and metastasis (29,31). The research on the molecular mechanisms of myofibroblasts promoting tumor progression have revealed that tumor-associated myofibroblasts, by participating in synthesis, deposition and remodeling of the extracellular matrix, producing some proteases, such as fibroblast activation protein, matrix metalloproteinases and urokinase plasminogen activator, promoting tumor angiogenesis, secreting soluble paracrine signals to stimulate proliferation of the tumor cell, and inducing tumor immune escape, thereby promoted tumor development (32-38).…”
Section: Relationship Between α α-Actin Expression Of Myofibroblasts mentioning
confidence: 99%
“…Probability of distant metastasis was predicted independently by immunohistochemical analysis of myofibroblastassociated a-SMA (Yamashita et al, 2010). Paracrine and autocrine communication between CAFs and cancer cells and CAFs and other stromal cells implicates multiple ligands, recognizing their cognate receptor on the partner cell; it contributes to the transition from the "normal" to the pro-tumoral state of the stromal cells (Mareel et al, 2009).…”
Section: Myofibroblasts and Desmoplasiamentioning
confidence: 99%